Tecnologías de la información y comunicación y la participación estudiantil en el proceso de enseñanza aprendizaje en el Colegio de Bachillerato 27 de Febrero - González Toledo, Jessenia Ivanova (2023)
Student participation within an educational institution should be primary for the teaching-learning process, to which we must add the implementation of information and communication technologies (ICT) that help to promote these practices for the benefit of students. Therefore, it is necessary to show the relationship between the use of ICT and student participation in the teaching-learning process. Through the study of ICT and student participation in the teaching-learning process carried out at the 27 de Febrero High School, in which a quantitative approach was used, with a non- experimental design, correlational and cross-sectional scope, in addition the analytical- synthetic and deductive methods were employed to analyze student participation and the use of ICT. Findings suggest that, although the initial hypothesis proposing a positive relationship between the increased use of ICTs by teachers and student participation, there are real- world limitations hindering effective implementation. Considering that the degree of student participation obtained in the research was minimal , the activities carried out by students focused on participation through ICT are infrequent, based on this determination it can be established that the relationship in the teaching-learning process according to the results, suggest that the use of ICT by teachers is not yet widespread , many teachers use ICT in a limited way, without taking advantage of its full potential to enhance the teaching process and student participation, and therefore its influence on academic performance, although it was identified that students with 63. 6% sometimes perform activities in programs focused on student participation. It is important to take these limitations into account in order to address them and promote a more extensive and effective use of technologies in the educational environment, which could lead to increased participation and enrichment of theteaching-learning process.